2019
DOI: 10.1080/21691401.2019.1699821
|View full text |Cite
|
Sign up to set email alerts
|

c(RGDyk)-modified nanoparticles encapsulating quantum dots as a stable fluorescence probe for imaging-guided surgical resection of glioma under the auxiliary UTMD

Abstract: Surgical resection remains the preferred approach for some patients with glioblastoma (GBM), and eradication of the residual tumour niche after surgical resection is very helpful for prolonging patient survival. However, complete surgical resection of invasive GBM is difficult because of its ambiguous boundary. Herein, a novel targeting material, c(RGDyk)-poloxamer-188, was synthesized by modifying carboxyl-terminated poloxamer-188 with a glioma-targeting cyclopeptide, c(RGDyk). Quantum dots (QDs) as fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Surgical resection, chemotherapy and radiotherapy are important therapies for glioma patients [ 6 ]. Since most gliomas expand during aggressive growth, resulting in an unclear boundary between the tumor and normal brain tissues, and the glioma cells infiltrate the brain and migrate from the tumor [ 7 ]. Thus, it is very difficult to completely remove the tumor by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection, chemotherapy and radiotherapy are important therapies for glioma patients [ 6 ]. Since most gliomas expand during aggressive growth, resulting in an unclear boundary between the tumor and normal brain tissues, and the glioma cells infiltrate the brain and migrate from the tumor [ 7 ]. Thus, it is very difficult to completely remove the tumor by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the proposed NPs show an efficient labeling of both the glioblastoma margin and inner tumor area after in vivo administration (Figure 7b). Nevertheless, recent studies showed the specific relevance of other cRGD‐decorated nano‐based technologies (quantum dots [QDs] 116 and dendrimers 30 ) capable of efficiently imaging glioblastoma tumor margins. Importantly, the great potential of QDs for the detection and treatment of glioblastoma has been widely discussed also by Kantelhardt et al, where these nanosystems were coupled with monoclonal antibodies against EGFR, highly upregulated in many gliomas 117 …”
Section: Nanosystems For Fgsmentioning
confidence: 99%
“…To enhance fluorescence properties, cancer selectivity, and uptake, the proposed agents exploit different platforms, including peptide-based compounds, [24][25][26] lipid antitumor agents (alkylphosphocholine [APC] analogs), 27,28 inorganic materials (lanthanide metal complexes), 29 and nanosystems (RGD peptide-decorated nanocarriers, theranostic photonic nanoprobes, polymer-based nanoparticles [NPs], etc.). [30][31][32] with a Phase III multicenter randomized clinical trial on the impact of 5-ALA in high-grade glioma (HGG) surgery. 34 Their multivariate analysis demonstrated that complete resection of the enhancing portion of HGG occurred in 65% of patients assigned to the 5-ALA group versus 36% in those assigned to conventional white light.…”
mentioning
confidence: 99%
“…Quantum dots (QDs) are small (~2–10 nm) luminescent semiconductor nanocrystals that combine the merits of the aforementioned nanoparticles including the induction of a cytotoxic effect, effective penetration of the BBB and deliverance of drugs to the tumor site [ 181 , 182 ]. The spectrum of properties of QDs, their high tumor selectivity and their potential as fluorescence probes opens new possibilities for image-guided drug delivery and resection of gliomas [ 183 , 184 ]. Their photophysical properties may also facilitate bioimaging [ 185 ].…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%